2003
DOI: 10.1074/jbc.m308336200
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Snail Family Transcription Repressors Regulate Chondrocyte, Extracellular Matrix, Type II Collagen, and Aggrecan

Abstract: Snail family genes are conserved among species during evolution and encode transcription factors expressed at different stages of development in different tissues. These genes are involved in a broad spectrum of biological functions: cell differentiation, cell motility, cell cycle regulation, and apoptosis. However, little is known about the target genes involved in these functions. Here we show that mouse Snail family members, Snail (Sna) and Slug (Slugh), are involved in chondrocyte differentiation by contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 45 publications
4
58
0
Order By: Relevance
“…For cartilage-specific genes, these include δEF1, AP-2α, Snail, Slug, Twist1, and C/EBPβ. [18][19][20][21][22] Among these, δEF1, AP-2α, and Twist1 are expressed by chondrocyte progenitors and maintain their undifferentiated state. 18,20,21,23 Their expression in the salivary gland was therefore compared with their expression in pleomorphic adenoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For cartilage-specific genes, these include δEF1, AP-2α, Snail, Slug, Twist1, and C/EBPβ. [18][19][20][21][22] Among these, δEF1, AP-2α, and Twist1 are expressed by chondrocyte progenitors and maintain their undifferentiated state. 18,20,21,23 Their expression in the salivary gland was therefore compared with their expression in pleomorphic adenoma.…”
Section: Discussionmentioning
confidence: 99%
“…17 Negative regulators include δEF1, AP-2α, Snail, Slug, Twist1, and C/EBPβ. [18][19][20][21][22] Snail, Slug, and C/EBPβ are expressed by hypertrophic chondrocytes, which indicates that they control terminal chondrocyte differentiation and promote endochondral ossification; 11,19,22 δEF1, AP-2α, and Twist1 are expressed by chondroprogenitors, which indicates that they control early-phase chondrogenesis. 18,20,21,23 The aim of our study was to clarify the mechanisms behind chondrogenesis in pleomorphic adenoma epithelial cells.…”
mentioning
confidence: 99%
“…A number of genes involved in cell-cell or cell-matrix interactions, such as E-cadherin, 27 fibronectin, 18 collagen type II, 28 appear to be regulated by the Snail family of transcription factors. Some of them regulate cell movements during early embryogenesis.…”
Section: Nrz Controls Gastrulation Via a Snail-1-dependent Pathwaymentioning
confidence: 99%
“…We substantially confirmed earlier immunohistochemical and electron microscopy findings by Parkkinen et al 38 These authors showed in fact redistribution, whorl formation, and autophagy of the ER in polyamine-deprived BHK cells. This is of particular interest in view of recent in vitro studies 39,40 demonstrating that disturbances of the ER homeostasis results in a EMT-like process characterized by cell morphology changes and extensive reorganization of the actin cytoskeleton. 2,39,40 In our model, endocellular polyamine depletion dramatically enhances TGFb 1 -induced EMT, by increasing at the same time the expression of typical ER-stress proteins like GRP78 and GRP94, thus suggesting a direct involvement of ER-stress in the overall and polyamine depletion-dependent scenario.…”
Section: Discussionmentioning
confidence: 99%